P351Pretreatment of mesenchymal stem cells does not enhance their recruitment to injured tissue in a model of ischemia-reperfusion injury yet abolishes their anti-inflammatory capabilities. (15th July 2014) - Kavanagh, D; Boulton, A; O'leary, M; Suresh, S; Newsome, PN; Kalia, N
Abstract: Purpose: Considerable interest surrounds the use of Mesenchymal Stem Cells (MSC) as therapeutics, primarily due to their low immunogenicity and ability to secrete paracrine mediators. While MSCs possess the potential to modify inflammatory injury, recruitment to injured tissues is generally poor. We investigated whether ex vivo pretreatment with cytokines or chemical factors could enhance MSC recruitment to injured tissues. We also considered whether these techniques could influence the therapeutic ability of MSCs following ischemia-reperfusion (IR) injury. Methods: Using in vitro and in vivo assays, we investigated both the adhesive and anti-inflammatory capabilities of primary murine PDGFRα+ MSCs (mMSCs) following pretreatment. For some in vitro treatments, we compared the behaviour of mMSCs to primary human MSCs (hMSCs). MSCs were treated with CXCL12, TNFα, IFNγ, H2O2 or PBS for 1 hour. Adhesion was investigated using immobilized adhesion proteins, cultured endothelium and intravital microscopy of the small intestine. To assess inflammation, neutrophil recruitment was monitored in vivo following IR injury of the small intestine (neutrophils labelled with PE-conjugated anti-Gr-1). Tissue blood flow was investigated using Laser Doppler. Results: Prior treatment of mMSCs did not enhance cell adhesion to the protein ligands ICAM-1, VCAM-1 or MAdCAM-1. Similarly, mMSC adhesion to murine colonic or cardiac endothelium was not enhanced following pretreatment. Conversely, adhesion of hMSCs to cardiac endothelium was significantly (p<0.001) enhanced following pretreatment with CXCL12 or IL-8. In an in vivo intestinal model of IR injury, mMSC recruitment was not increased in response to injury and could not be enhanced using any of the pretreatment strategies tested. Although mMSCs were not recruited to injury per se, their presence was able to significantly (p<0.05) reduce neutrophil accumulation in the jejunal villous microcirculation following IR injury. Tissue blood flow was significantly (p<0.05) enhanced in early reperfusion in mice receiving mMSCs. Pretreatment of mMSCs with TNFα abolished their ability to reduce neutrophil accumulation and improve flow. Treatment of mMSCs with TNFα resulted in significant (p<0.001) release of IL-6 (vs control). Conclusions: MSC recruitment to the IR injured murine intestine is not enhanced by the pretreatment regimes tested. Nevertheless, MSCs - when not pre-treated - were able to reduce inflammation following IR. Future studies involving MSCs (basic and clinical) should pay careful consideration to the use of pretreatment strategies.